2016
DOI: 10.1080/00480169.2016.1236710
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a hydrogel liquid bandage in 30 dogs undergoing tibial plateau levelling osteotomy surgery

Abstract: Due to several disadvantages of traditional bandaging, which can require post-operative maintenance and removal, lasts only a short time, and be painful when removed, an alternative with fewer drawbacks is desirable. HLB may present such an alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…12 Therefore, several strategies have been employed clinically to attempt to lower the rate of infection, including use of antibiotic impregnated suture, extended postoperative antimicrobials, and implementation of preventive intraoperative and postoperative protocols. 6,9,11,[13][14][15] The objective of a systematic review is to identify, evaluate, and summarize the findings of all relevant individual studies about a specific issue, thereby making the available evidence more accessible to individuals and allowing them to make informed decisions. The objective of the systematic review reported here was to evaluate published data that could be used to determine whether the use of extended postoperative antibiotics after TPLO in dogs would reduce the risk of SSI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Therefore, several strategies have been employed clinically to attempt to lower the rate of infection, including use of antibiotic impregnated suture, extended postoperative antimicrobials, and implementation of preventive intraoperative and postoperative protocols. 6,9,11,[13][14][15] The objective of a systematic review is to identify, evaluate, and summarize the findings of all relevant individual studies about a specific issue, thereby making the available evidence more accessible to individuals and allowing them to make informed decisions. The objective of the systematic review reported here was to evaluate published data that could be used to determine whether the use of extended postoperative antibiotics after TPLO in dogs would reduce the risk of SSI.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in a recent study found that the cost of treating an SSI approached 50% of the original surgery cost and, in some, cases exceeded it 12 . Therefore, several strategies have been employed clinically to attempt to lower the rate of infection, including use of antibiotic impregnated suture, extended postoperative antimicrobials, and implementation of preventive intraoperative and postoperative protocols 6,9,11,13‐15 …”
Section: Introductionmentioning
confidence: 99%
“…Surgical site infection (SSI) is one of the most common complications after TPLO (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). SSI undoubtedly has a negative impact on patient well-being, client satisfaction, and financial burden and often necessitates an additional anesthetic episode and surgical procedure for implant removal (19).…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5,14,18,19 The use of postoperative wound dressings is not a standardized practice and there have been few veterinary studies evaluating their efficacy. [20][21][22] Potential benefits of postoperative wound dressings include protection from the environment and from patient self-trauma, both of which limit exposure to bacterial contamination. In a review on dressing use and SSI rate in human medicine, no significant difference was identified in the risk of SSI rate between patient groups in which a dressing was applied and those in which the wound was left uncovered.…”
Section: Introductionmentioning
confidence: 99%